Michael addition of P-nucleophiles to azoalkenes provides simple access to phosphine oxides bearing an alkylhydrazone moiety - Kokuev, Alexandr O.; Sukhorukov, Alexey Yu. (Frontiers in Chemistry, 2023)
β-Hydrazonophosphine oxides are precursors of useful organophosphorus compounds, including phosphorylated N-heterocycles, alpha-aminophosphonates, vinylphosphonates, etc. In this work, a general transition metal-free synthesis of β-hydrazonophosphine oxides was developed. The method relies on the Michael addition of phosphine oxides R2POH to reactive azoalkenes (1,2-diaza-1,3-butadienes), which are generated in situ from alpha-halohydrazones and Hunig’s base. The reaction stereoselectively leads to Z-isomers of β-hydrazonophosphine oxides that are stabilized by intramolecular hydrogen bonding. The conversion of the products thus obtained into potential chelating ligands was showcased.